Generating direct diamond shaping tool paths using special-purpose computer-aided-machining post-processor. Issue 9 (2nd September 2022) - Low, Darren Wei Wen; Tan, Nicholas Yew Jin; Wee Keong, Dennis Neo; Senthil Kumar, A.
ABSTRACT: Ultra-precision direct diamond shaping (DDS) is an attractive method for manufacturing highly accurate and complex features. DDS employs 4 of the 5-axes in an Ultra-Precision Machine (UPM) with a conventional diamond tool to machine features on a workpiece mounted on a rotary axis. It has been proven to be effective and flexible in manufacturing intricate features, from microfluidics to Fresnel lenses. However, a significant technical hurdle in the practical implementation of DDS is the complexity of its non-conventional tool path generation. Current practices in generating DDS tool paths rely on programming and significant mathematical manipulation. This is not only time consuming but also requires the user to overcome a steep learning curve. Moreover, conventional Computer-Aided Machining (CAM) software does not support DDS tool paths, but instead supports tool path generation for common machining processes like milling and turning. This paper discusses the use of a special-purpose post processor to bridge the compatibility gap between CAM and DDS tool path generation. The mathematics and logic of converting CAM milling tool paths to DDS would be discussed. Finally, the post processor was experimentally verified using a case study.